Сарматський воїнський могильник на Середньому Пруті - Курчатов, С.І.; Симоненко, О.В.; Чирков, A.Ю. (Археологія, 1995)
У статті вводяться до наукового обігу та інтерпретуються результати досліджень пізньосарматського (друга половина II — перша половина III спи) могильника поблизу с. Нові Бедражі в Молдові, що входить до кола специфічних для цього регіону пам’яток з ритуальними квадратними ровами. На думку авторів, ця інновація в сарматській культурі с наслідком контактів сарматів з кельто-германським світом. В 1988 г. у с. Новые Бедражи в Молдове был исследован позднесарматский грунтовый могильник, состоявший из шести квадратных рвов и связанных с ними семи воинских захоронений. Рвы были расположены двумя рядами, ориентированы углами по сторонам света, средние размеры сооружений 12 х 12 м. Погребения располагались у юго-западных углов сооружений. Впервые на памятниках этого типа зафиксирована устойчивая связь погребений со рвами. Датирующий материал (мечи с кольцевым навершием, сильнопрофилированная фибула причерноморского типа, пряжки позднесарматских типов, краснолаковая керамика) позволяет отнести могильник ко второй половине II — первой половине III в. Могильник у с. Новые Бедражи входит в круг специфичных для Северо-Западного Причерноморья сарматских памятников, где на грунтовых могильниках появляется инновация — расположенные рядами квадратные рвы, не содержащие погребения во внутреннем пространстве. Изучение генезиса этого обряда позволяет считать его результатом контактов сарматов Северо-Западного Причерноморья с кельто-германским миром во второй половине II в. Эти контакты могли осуществляться во время миграций готов на юго-восток. Появление подобного обряда у сарматов Альфельда и Нижнего Подонья в середине III в. должно связываться с расселением сарматов Северо-Западного Причерноморья на запад и восток после образования готского объединения. In 1988 near Novye Bedradgy village (Moldova Republic) the Late-Sarmatian cemetery consisting of the six square-shaped ditches and the seven tombs of warriors connected with them was uncovered. The ditches were disposed in two lines, orientated to the cordinal points by their comers, the mean dimensions of the constructions are 12 x 12 meters. The graves were disposed near the Sought-West comers of the ditches. The stable connection between the graves and ditches on the memorials of such type is fixed at the first time. The dating material (the swords with ring-shaped pommel, strongly profiled fibula of Black Sea-type, buckles of the Late-Sarmatian types, red-coated pottery) permits to date the cemetery to the second half of 2nd-first half of 3rd cent. A. D. The cemetery near Novye Bedradgy could be included to the range of the specific for the North-West Pontic Area Sarmatian memorials where the innovation — the square-shaped ditches disposing in lines and having no graves inside — appears. The study of the genesis of this custom permits to recognize it as a result of the contacts between the Sarmatae of North-West Pontic Area and the Celtic-German world in the second half of 2nd cent. A. D. These contacts may be realized during the Gothic migrations to Sought-East. The appearance of such custom among the Sarmatae of Alfold and Lower Don Basin in the middle 3rd cent. A. D, ought to be connected with the settling of the Sarmatae of North-West Pontic Area to West and East after formation of the Gothic union.